La gamificación y su aplicación en estudiantes con bajo rendimiento académico - Montero Llamuca, Leonor Beatriz (2022)
The subject of this research work is called "Gamification and its application in students with low academic performance", which is elaborated from the problems that occurred in students of Higher Basic Education of the Educational Unit "Pablo Hannibal Vela Egüez" and their low academic performance. In this sense, the use of gamification was proposed as an option to benefit students in these conditions, since the bibliographic review served as empirical support about its benefits in the area of learning, by allowing that through the mechanics of games, the student feels motivated in the development of the different subjects. In this way, data collection techniques were applied to the teachers and authorities of the institution, such as the interview, the survey and the attitude escalation, to collect the information that supports the proposal of the guide for the application of gamification with the purpose of promoting the academic performance of students. As a result of the aforementioned, both the need for teachers to have a guide with the necessary information to be able to apply gamification in their classrooms, as well as the favorable attitude to use this type of instruments, was evidenced……….